PERAN FILSAFAT ILMU DALAM PERKEMBANGAN STUDI ISLAM - Akhmad Zaeni; Ahidul Asror; Imam B. Juhari (Al-Fikru : Jurnal Pendidikan Dan Sains, 2023)
The development of scientific progress is a necessity, this includes all sciences, both politics, economics, natural sciences, and so on, including Islamic education which is also experiencing very rapid development. This includes being influenced by the development of the philosophy of science, there are at least 4 phases in the philosophy of the development of science, namely: the initial phase to the renaissance, then the positivism phase, the modern phase to the contemporary phase. Likewise, Islamic studies also experienced developments starting from the classical, modern and contemporary periods, and in this contemporary period it was divided into 5 trends, namely: fundamentalist, traditional, reformistic, posttraditionalistic and modernistic. The development of Islamic science is at least influenced by 3 reasons: to meet the material and spiritual needs of Muslims need Islamic science, the burial of metaphysical aspects, or aspects that cannot be measured in the lab by western science and the need for Islamic science by Muslims who are in an area where . the development of contemporary science with a culture that is not the same as the west. And to answer and resolve all the problems above, it is necessary to present a philosophy of science in the development of Islamic science (Islamic studies). The purpose of this research is to briefly discuss the contribution of the philosophy of science to the growth of Islamic studies. The research method used is a qualitative approach, using data analysis using data reduction, presenting data, drawing conclusions. Alltypes of knowledge that humans need as servants of God are the creation of laws that are permissible and must. The scientist does not limit himself to his own field of study but on the contrary he must look to fields which are close to developing a science whose impact does not prohibit greed of material possessions but on realist, ethical, harmonious, and religious presuppositions. However, the author appreciates the approach that claims that knowing alittle (particular) is better than knowing a little (general) things.Keywords: Philosophy of Science, Development, Islamic Studies